Peningkatan Perilaku tentang Diet Sehat di Panti Asuhan Yatim Piatu dan Dhuafa Yayasan Al ‘Ashr Banjarmasin 2019 - Yeni Riza; Erwin Ernadi; Mahmudah Mahmudah (Jurnal Abdimas Kesehatan (JAK), 2020)
A healthy lifestyle is an effort that someone does consistently to stay in a healthy and optimal condition. Healthy lifestyle is done by paying attention to the nutritional needs in the body, exercise, rest and positive thinking. Healthy lifestyle is not uncommon as an effort that is not easy so it is difficult to implement, even though it will be even more difficult if we have become sick because they do not run a healthy lifestyle. The Orphanage Orphanage and Dhuafa Foundation Al ‘Ashr Banjarmasin is one of the orphanages in the city of Banjarmasin. Imbalance between food consumed with needs is the cause of malnutrition problems and over nutrition problems, so that children in this orphanage also have the risk of under nutrition problems and more due to lack of knowledge about a healthy diet. Therefore This community service activity will be held for children and adolescents of the Orphanage Orphanage and Dhuafa Foundation Al 'Ashr Banjarmasin in order to prevent nutritional problems due to inappropriate dietary patterns. The purpose of the activity is to provide knowledge for children and young people of the Orphanage Orphanage and Dhuafa Foundation Al ‘Ashr Banjarmasin on a healthy diet for the body's needs to create a healthy young generation. The main targets or specific targets of this activity are children and young people of the Orphanage Orphanage and Dhuafa Foundation Al ‘Ashr Banjarmasin which is located at Jalan Tembus Perumnas Rt 45 No. 127 Banjarmasin City. The method used in this activity is through video screenings, lectures, and discussions and questions and answers. The counseling activity was carried out on December 8, 2019, attended by 18 orphans. Activities take place smoothly and in an orderly manner. Increased knowledge about healthy diets in adolescents at the Orphanage Orphanage and the Al r Ashr Foundation Dhuafa, Increased skills in carrying out body examinations conducted independently such as measuring waist circumference, heart rate tests, oral health, nails etc